Testicular infarction in a patient with sickle cell anemia: A case report: : A case report - ALSulmi, Hussam A. (International Journal of Health Sciences, 2018)
Sickle cell anemia is one of the common inherited hemoglobinopathy disorders. It affects patient quality of life through different types of complications. Brain, lung, kidney, spleen, and bone marrow commonly affected; however, testicular infarction is rarely happened. This is a 29-year-old Saudi male who is known for sickle cell disease (SCD). He presented with left scrotal pain and swelling for 1 week which did not respond to antibiotic. Scrotal ultrasound showed swollen heterogeneous hypoechoic left testicle with no blood flow, suggesting testicular infarction. Despite medical treatment, the patient went for orchiectomy. Pathology revealed extensive testicular infarction. Up to our knowledge, this is the first case report of testicular infarction in SCD in Arab countries, and the sixth case reported worldwide. Early diagnosis and doing unnecessary surgical intervention still unavoidable as there is lack of information. We think writing the first case of testicular infarction in sickle cell patients with Arab haplotype is worthful and it will add to the literature.